STUDY OF PATHOGENETIC FEATURES INFECTIOUS CAUSED BY HIGHLY PATHOGENIC INFLUENZA VIRUS A/H5N1 IN WILD DUCKS AND DOMESTIC CHICKEN - E. R. Abdullazyanova; A. V. Zajkovsmaya; L. V. Shestopalova; A. M. Shestopalov (Acta Biomedica Scientifica, 2012)
Changes in lung, liver and brain were investigated, in wild, ducks and. domestic chicken under experimental infection caused by highly pathogenic avian Influenza virus A/H5N1. Isolation of virus was demonstrated, in swabs from the throat and. cloaca, virus titers were presented, in patterns of organs. Changes in organs of wild, ducks have dystrophic characteristics, but in domestic chickens are of the dystrophic and necrotic nature.